The THE FUNCTION OF MUSIC AS A MEDIA OF DAWAR IN GAMBUS MISRI PERFORMANCES : FUNGSI MUSIK SEBAGAI MEDIA DAKWAH DI DALAM PERTUNJUKAN GAMBUS MISRI - Firmansyah, Rizki; Hidajad, Arif (Solah, 2025)
Gambus Misri is an Islamic art form originating from the Jombang region. Gambus Misri originates from a genre of gambus music that historically originated in the Middle East. Over time, gambus music entered the Indonesian archipelago and became a distinctive form of Malay music, giving rise to classical Malay gambus music that became the forerunner of music in Gambus Misri performances. Gambus Misri music is not only an accompaniment to a performance, but also contains values. The values contained in Gambus Misri music convey a message about Islamic teachings that originated from an Islamic culture that developed in Islamic boarding schools in the Tebuireng area in the 1960s. The messages contained have deep meaning in Islamic teachings, which is a primary function of music, which aims to serve as a medium of da’wah in spreading Islam in society. Gambus Misri music has an important function in community culture. Music is not only a complement, but an inseparable part of the entire form of the performance. Through its integrated structure and function, Gambus Misri music asserts itself as a living, meaningful cultural heritage worthy of continued preservation.